Flood Insurance in New York City Following Hurricane Sandy - Lloyd Dixon, Noreen Clancy, Bruce Bender, Aaron Kofner, David Manheim, and Laura Zakaras (RAND Corporation, 2013)
This report provides the most-comprehensive data to date on flood insurance coverage in New York City both before and after Hurricane Sandy made landfall on October 29, 2012. It also examines the consequences of changes to the National Flood Insurance Program and the update of the Federal Emergency Management Agency’s flood insurance rate map for the city’s residents in the wake of Hurricane Sandy. It is hoped that this work will provide information needed for discussions of proposed policy options for mitigating risk and making insurance premiums more affordable in the future. The research was supported by the New York City Mayor’s Office of Long-Term Planning and Sustainability, and initial results provided background data on flood insurance for the City’s recent report, A Stronger, More Resilient New York, released June 2013.1